2017
DOI: 10.1093/rpd/ncw370
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Radiofrequency Electromagnetic Fields From Wi-Fi in Australian Schools

Abstract: The increasing use of Wi-Fi in schools and other places has given rise to public concern that the radiofrequency (RF) electromagnetic fields from Wi-Fi have the potential to adversely affect children. The current study measured typical and peak RF levels from Wi-Fi and other sources in 23 schools in Australia. All of the RF measurements were much lower than the reference levels recommended by international guidelines for protection against established health effects. The typical and peak RF levels from Wi-Fi i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 7 publications
3
32
0
Order By: Relevance
“…In an animal study, Hassanshahi et al [16] demonstrated that Wi-Fi radiation had possible adverse effects on cross-modal and unimodal novel object recognition. An important issue is the level of RF exposure from Wi-Fi in schools and public areas [17][18][19]. The International Commission on Non-Ionizing Radiation Protection published guidelines regarding the limits of exposure to non-ionizing radiations [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an animal study, Hassanshahi et al [16] demonstrated that Wi-Fi radiation had possible adverse effects on cross-modal and unimodal novel object recognition. An important issue is the level of RF exposure from Wi-Fi in schools and public areas [17][18][19]. The International Commission on Non-Ionizing Radiation Protection published guidelines regarding the limits of exposure to non-ionizing radiations [20].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown that the exposure to RF fields from Wi-Fi in public places is expected to be much lower than these limits. For example, Karipidis et al [17] measured typical and peak RF levels from Wi-Fi and other sources in 23 schools in Australia. They found that the RF exposure in children from Wi-Fi at school was very low and comparable to, or lower than, other sources in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing use of Wi‐Fi and Wi‐Fi enabled devices in schools, there has been a growing concern among parents regarding RF‐EMR exposure from Wi‐Fi and potential effects on their children's health 10 . Children in schools are exposed to Wi‐Fi exposures voluntarily or involuntarily – either from Wi‐Fi enabled devices or Wi‐Fi routers, respectively.…”
Section: Rf‐emr Exposure Guidelinesmentioning
confidence: 99%
“…Until recently, there have been little data available regarding children's Wi‐Fi exposures 11,12 . Recently, two independent groups of Australian researchers have published findings on children's exposures to Wi‐Fi in kindergartens and schools 10,13 . These data are amongst the first comprehensive Wi‐Fi exposure measurements in these settings.…”
Section: Rf‐emr Exposure Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation